(untitled) (International Educators Conference, 2025)
With an incidence of five to eight per thousand newborns, congenital heart defects (CHD) are the most common congenital anomalies. As approximately half of the CHDs are severe and treatment carries risks, CHDs are a large contributor to infant mortality worldwide. Due to continuous improvement of ICU-care and cardiothoracic surgery, together with increased prenatal detection, survival rates of affected newborns have increased greatly. For that reason, the focus of innova tion has shifted from increasing survival rates to improvement of long-term (neuro) developmental outcomes.